HADAPI COBAAN DENGAN BERPIKIR POSITIF DAN SABAR BERLANDASKAN AL QUR’AN - Rusdiah, Rusdiah (Sekolah Tinggi Agama Islam (STAI) Al-Ma'rif Buntok, 2023)
Every test and trial that comes, Allah gives with the aim of maturing ourselves, mature in mind, heart and attitude. Trials and trials are everyday friends that are very familiar to us. Tests and trials can make us become someone else, become something we are not, even make us stressed and go crazy. Every test and trial must have a solution. To face the test, one must always think positively and be patient. Disasters do not come except because of sin. In this way, you can remember what has been done to get hit by a disaster like this. In this way, there will be more istighfar. Disasters sometimes come not because of sin, but because God still cares and to be closer to the Creator. Disasters also come so that a human being can rise in rank in the sight of Allah. With this, you will always be grateful because you have had a disaster that produces goodness and profit.